Pastoraat in rousmart as bewuste kommunikasie van die emosies van rousmart 1 - Smith, W. (Hervormde teologiese studies, 2000)
New meaning of life within grief. From the perspecive of pastoral care and counselling, one often finds that people experience a lack of meaning in their lives when confronted with grief. Thesalvation through Jesus Christ, and the way it is incorporated in one's life, doesn't bring existential hope and meaning any more. This article attempts to give new meaning to an old discussion of "grief" the conscious and unconscious mind, aswell as the emotions of grief, in such a way that new meaning of life within grief becomes a spiritual way of living, a life coram Deo.